Abatacept treatment for patients with early active primary Sjögren's syndrome: a single-centre, randomised, double-blind, placebo-controlled, phase 3 trial (ASAP-III study). (March 2020) - van Nimwegen, Jolien F; Mossel, Esther; van Zuiden, Greetje S; Wijnsma, Robin F; Delli, Konstantina; Stel, Alja J; van der Vegt, Bert; Haacke, Erlin A; Olie, Lisette; Los, Leonoor I; Verstappen, Gwenny M; Pringle, Sarah A; et al.
Summary: Background: Several small open-label studies have suggested efficacy of abatacept—a co-stimulation inhibitor—in patients with primary Sjögren's syndrome. These promising results warranted further evaluation. We therefore aimed to further assess the safety and efficacy of abatacept compared with placebo in patients with primary Sjögren's syndrome. Methods: We did a single-centre, randomised, double-blind, placebo-controlled, phase 3 trial at the University Medical Center Groningen (Groningen, Netherlands). We included patients with primary Sjögren's syndrome fulfilling the American–European Consensus Group criteria, aged 18 years or older, with positive salivary gland biopsies, time from diagnosis of 7 years or less, and a European League Against Rheumatism Sjögren's Syndrome Disease Activity Index (ESSDAI) score of 5 or more. Independent pharmacists randomly allocated patients (1:1) to either the abatacept group or placebo group using a computer-generated sequence stratified by previous use of disease-modifying anti-rheumatic drugs. Patients received at-home subcutaneous injections of abatacept (125 mg) or placebo once a week for 24 weeks. The primary outcome was the between-group difference in ESSDAI score at week 24. Efficacy was analysed in patients who received at least one drug dose and for whom post-baseline data were collected. Safety was analysed in all patients who received at least one drug dose. Findings: Between Aug 14, 2014, and Aug 23, 2018, 580 patients were reviewed for eligibility, of which 80 patients were randomly assigned to receive study treatment. Efficacy was analysed in 40 patients receiving abatacept and 39 patients receiving placebo (one patient in this group was lost to follow-up). The primary outcome did not significantly differ between the treatment groups. The adjusted mean difference in ESSDAI score at week 24 between the abatacept group and placebo group was −1·3 (95% CI −4·1 to 1·6). No deaths or treatment-related serious adverse events occurred. In 38 (95%) of 40 patients in the abatacept group, 103 adverse events occurred, including one serious adverse event and 46 infections. In 38 (95%) of 40 patients in the placebo group, 87 adverse events occurred, including four serious adverse events and 49 infections. Interpretation: On the basis of this trial, we cannot recommend abatacept treatment as standard of care to reduce systemic disease activity in patients with primary Sjögren's syndrome. Further studies should evaluate whether patients with specific clinical manifestations and biological characteristics might benefit from abatacept treatment. Funding: Bristol-Myers Squibb.